Pre-service teachers’ beliefs about linguistic and cultural diversity in schools: the role of opportunities to learn during university teacher training - Paetsch, Jennifer; Heppt, Birgit; Meyer, Jakob (Frontiers in Education, 2023)
We investigated pre-service teachers' beliefs about linguistic and cultural diversity in schools and the extent to which these beliefs differ between students at the beginning and at the end of university teacher training using a sample of 1,319 pre-service teachers at different stages of study from a large public university in Germany. Given the cross-sectional nature of our data, comparisons of the different student groups (Semesters 1-2 vs. Semester 6+) were based on a propensity score matching approach. We further examined the relationship between pre-service teachers' beliefs and their opportunities to learn (OTL) using a subsample of 428 pre-service teachers. The findings suggest that beliefs about language-supportive teaching and egalitarian-but not multicultural-beliefs differed at the beginning and at the end of initial teacher training. Student teachers who studied German as a second language (GSL) more strongly endorsed beliefs about language-supportive teaching and egalitarian and multicultural beliefs than other students.